Mutation Profile And Tarv Resistance In People Living With Hiv Submitted To Genotyping Test In A Reference Laboratory In Belém Do Pará, Brazil - Bentaberry-Rosa, Alexandre Augusto; de Lima, Aline Cecy Rocha; da Costa, Maria Amélia de Oliveira; Dantas, Rubens Einar Corrêa; da Silva, Andréa Nazaré Monteiro Rangel; Monteiro, Jacqueline Cortinhas; Laurentino, Rogério Valois; Feitosa, Rosimar Neris Martins (Seven Editora, 2023)
To describe the presence of mutations and the ART resistance profile in PLHIV in Belém, Pará. Methods: This is a cross-sectional, descriptive and retrospective study, where 189 genotyping reports of individuals were included, regardless of age or sex and who were seen in the period from 2013 to 2015. Results: Most individuals had a high viral load (93%), low TCD4+ lymphocyte levels (97%) and the most prevalent HIV subtype was B (78%). We observed in this study a high presence of mutations in all classes of drugs used in ART with emphasis on M184V (ITRNN), K103N (ITRNN) and L63A/P/T/Q (PI), demonstrating that many mutations can contribute to the profile of viral resistance. Conclusion: The results presented show the importance of genotyping testing not only for choosing therapeutic and surveillance regimens, but also to contribute to patient adherence to antiretroviral treatment. DOI: https://doi.org/10.56238/colleinternhealthscienv1-100